Effect of vents on the output of hearing Aids (Bangladesh Journal of Otorhinolaryngology, 2012)
The aim of the study was to explore the effect of vents on the speech discrimination scores and electroacoustic characteristics of body level hearing aids. The Nineteen adults who participated in the study had mild to moderate sloping sensori-neural hearing loss and were in the age range of 18-70 years. Apart from 19 hearing aids users additional 11 hearing aids were also taken for the study of electro-acoustic characteristics only. Major changes in the electroacoustic characteristics of the body worn hearing aids was observed on HFA OSPL90, FOG and EINL which reduced to 7.31%, 9.19% and 7.72% when parallel vent of 2mm were bored in the regular ear moulds respectively. Parallel/ Diagonal vents improved the Speech Discrimination score by 9%. The cumulative impact of venting can be seen on improvement of speech discrimination scores and subjective impression of clear speech.DOI: http://dx.doi.org/10.3329/bjo.v18i1.10420   Bangladesh J Otorhinolaryngol 2012; 18(1): 59-62